Antiretroviral treatment for HIV infection: Swedish recommendations 2016. Issue 1 (2nd January 2017) - Eriksen, Jaran; Albert, Jan; Blaxhult, Anders; Carlander, Christina; Flamholc, Leo; Gisslén, Magnus; Josephson, Filip; Karlström, Olof; Navér, Lars; Svedhem, Veronica; Yilmaz, Aylin; Sönnerborg, Anders
Abstract: The Swedish Medical Products Agency and the Swedish Reference Group for Antiviral Therapy (RAV) have jointly published recommendations for the treatment of HIV infection on seven previous occasions (2002, 2003, 2005, 2007, 2009, 2011 and 2014). In February 2016, an expert group under the guidance of RAV once more revised the guidelines. The most important updates in the present guidelines are as follows: Tenofovir alafenamide (TAF) has recently been registered. TAF has several advantages over tenofovir disoproxilfumarate (TDF) and is recommended instead of TDF in most cases. First-line treatment for previously untreated individuals includes dolutegravir, boosted darunavir or efavirenz with either abacavir/lamivudine or tenofovir (TDF/TAF)/emtricitabine. Pre-exposure prophylaxis (PrEP) is recommended for high-risk individuals. As in the case of the previous publication, recommendations are evidence-graded in accordance with the Oxford Centre for Evidence Based Medicine (http://www.cebm.net/oxford-centre-evidence-based-medicine-levels-evidence-march-2009/ ) (Table 1 ). This document does not cover treatment of opportunistic infections and tumours.